Cyclic feeding regimen and balance between pro-oxidative and anti-oxidative processes in hepatocytes nuclei of young and old rats - Гірич, М. С.; Кургузова, Н. І.; Нікитченко, Ю. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The effect of cyclic feeding regimen on the dynamics of oxidative stress in hepatocytes nuclei of 3- and 19-month rats has been investigated. The intensity of pro-oxidative and anti-oxidative processes was evaluated by measuring of TBARs content and glutathioneperoxidase activity. The most pronounced oxidative stress was found to occur in young animals only after first cycle of periodic starvation/body weight recovery. The correlation between oxidative stress level and the activity of nuclear antioxidant system has been established. The decrease in the intensity of oxidative processes observed in the course of the second cycle of dietary restriction was interpreted as arising from adaptive mechanisms.